Analisis Pembinaan Olahraga Pelajar di Kabupaten Aceh Tenggara - Afrizal; M. Ikbal K (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
The Southeast Aceh District Government is currently developing student sports and is very supportive of this sports program. This is intended to create a synergy in the development of student sports in Southeast Aceh District and the efficient use of funds to increase sports achievement at the student level. The aims of this study were (1) to find out the planning, (2) organizing, (3) actuating, and (4) supervising the Southeast Aceh Regency Disparpora in improving the performance of its members in fostering student sports. The subjects in this study were the Tourism, Youth and Sports Office of Southeast Aceh District. This research seeks to collect data and information related to planning, organizing, actuating and supervising implementation management, breeding and sports coaching using descriptive methods and qualitative approaches. The instruments used to collect data are observation, interviews and documentation studies. Based on the results of the study, it can be concluded that the coaching mechanism carried out by the Southeast Aceh District Disparpora for student sports coaching is not as good as the management function of an organization, namely the process of planning, organizing, activating, and supervising.